How does household production affect measured income inequality? - Harley Frazis; Jay Stewart (Institute for the Study of Labor (IZA), 2009)
Although income inequality has been studied extensively, relatively little attention has been paid to the role of household production. Economic theory predicts that households with less money income will produce more goods at home. Thus extended income, which includes the value of household production, should be more equally distributed than money income. Previous studies have found this to be the case and have speculated that the more-equal distribution of extended income is due to the weak correlation between money income and household production income. We also find that extended income is more equally distributed than money income. The main contribution of our paper is that we identify the reason for this result. Our sensitivity analysis indicates that virtually all of the decline in measured inequality when moving from money income to extended income is due to the addition of a large constant the average value of household production - to money income and that measured inequality is insensitive to the correlation between money and household production income. The practical importance of this result is that estimates of extended income inequality are robust to imputation procedures and that researchers can obtain accurate estimates of trends by simply using mean values of household production income.
urn:nbn:de:101:1-20090323172
Keywords: D31; J22; D63; 330; Inequality; household production; Haushaltsproduktion; Einkommensverteilung; Zeitbudgetforschung; USA